Janke & Kunkel A. -G. - Janke & Kunkel AG (1930)
Business card for Janke & Kunkel A.G., a laboratory equipment manufacturer and trading company of pharmaceutical supplies. Founded in Cologne, Germany in 1910 by Curt Janke and Max Kunkel, the company faced destruction and upheaval during World War II. In 1948, the company revived itself as IKA-Works, Inc. which continues to produce laboratory equipment, and analytical and process technology today.
Keywords: Scientific apparatus and instruments; Chemical laboratories--Equipment and supplies; Machinery industry